Relation of Household Income to Access and Adherence to Combination Sacubitril/Valsartan in Heart Failure: A Retrospective Analysis of Commercially Insured Patients. Issue 7 (13th May 2022) - Johnson, Amber E.; Swabe, Gretchen M.; Addison, Daniel; Essien, Utibe R.; Breathett, Khadijah; Brewer, LaPrincess C.; Mazimba, Sula; Mohammed, Selma F.; Magnani, Jared W.
Abstract : Background: Outcomes in heart failure with reduced ejection fraction (HFrEF) are influenced by access and adherence to guideline-directed medical therapy. Our objective was to study the association between annual household income and: (1) the odds of having a claim for sacubitril/valsartan among insured patients with HFrEF and (2) medication adherence (measured as the proportion of days covered). We hypothesized that lower annual household income is associated with decreased odds of having a claim for and adhering to sacubitril/valsartan. Methods: Using the Optum de-identified Clinformatics Data Mart, patients with HFrEF and ≥6 months of enrollment for follow-up (2016–2020) were included. Covariates included age, sex, race, ethnicity, educational attainment, US region, number of prescribed medications, and Elixhauser Comorbidity Index. Prescription for sacubitril/valsartan was defined by the presence of a claim within 6 months of HFrEF diagnosis. Adherence was defined as proportion of days covered ≥80%. We fit multivariable-adjusted logistic regression models and hierarchical logistic regression accounting for covariates. Results: Among 322 007 individuals with incident HFrEF, 135 282 had complete data for analysis. Of the patients eligible for sacubitril/valsartan, 4.7% (6372) had a claim within 6 months of HFrEF diagnosis. Following multivariable adjustment, individuals in the lowest annual income category (<40 000) were significantly less likely (odds ratio, 0.83 [95% CI, 0.76–0.90]) to have a sacubitril/valsartan claim within 6 months of HFrEF diagnosis than those in the highest annual income category (≥100 000). Annual income <40 000 was associated with lower odds of proportion of days covered ≥80% compared with income ≥100 000 (odds ratio, 0.70 [95% CI, 0.59–0.83]). Conclusions: Lower household income is associated with decreased likelihood of a sacubitril/valsartan claim and medication adherence within 6 months of HFrEF diagnosis, even after adjusting for sociodemographic and clinical factors. Future analyses are needed to identify additional social factors associated with delays in sacubitril/valsartan initiation and long-term adherence.